2017
DOI: 10.1037/gpr0000119
|View full text |Cite
|
Sign up to set email alerts
|

Power and Persuasion: Processes by Which Perceived Power Can Influence Evaluative Judgments

Abstract: The present review focuses on how power—as a perception regarding the self, the source of the message, or the message itself—affects persuasion. Contemporary findings suggest that perceived power can increase or decrease persuasion depending on the circumstances and thus might result in both short-term and long-term consequences for behavior. Given that perceptions of power can produce different, and even opposite, effects on persuasion, it might seem that any relationship is possible and thus prediction is el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 151 publications
(197 reference statements)
0
15
0
1
Order By: Relevance
“…The implications of the meaning postulate extend beyond ease effects to other variables associated with default high validity. For example, head nodding is associated with agreement (Wells & Petty, 1980), smiling is a positive emotional sign associated with pleasantness or confidence (Paredes et al, 2013), and feeling powerful is often experienced as a desirable state (Briñol, Petty, Durso, & Rucker, 2017). Because the default meaning of these variables is typically positive and associated either with correctness or pleasantness, they often lead to one's salient thoughts being seen as more valid.…”
Section: Different Meanings Of Default High Validity Variablesmentioning
confidence: 99%
“…The implications of the meaning postulate extend beyond ease effects to other variables associated with default high validity. For example, head nodding is associated with agreement (Wells & Petty, 1980), smiling is a positive emotional sign associated with pleasantness or confidence (Paredes et al, 2013), and feeling powerful is often experienced as a desirable state (Briñol, Petty, Durso, & Rucker, 2017). Because the default meaning of these variables is typically positive and associated either with correctness or pleasantness, they often lead to one's salient thoughts being seen as more valid.…”
Section: Different Meanings Of Default High Validity Variablesmentioning
confidence: 99%
“…The power of authorities has long been observed in the literature (for an extensive review, see Cialdini & Goldstein, 2004). The mention of the professor, an authority fi gure, may have acted as a peripheral cue, guiding a peripheral attitude change (Briñol, Petty, Durso, & Rucker, 2017). With little participant motivation to elaborate the proposal, the professor's status could have had more weight on the evaluation, acting as a heuristic.…”
Section: Discussion Of Experimentsmentioning
confidence: 99%
“…Indeed, some trends emphasize feeling powerful as a means of becoming more successful across different domains of life (Burgmer & Englich, 2012;Lammers et al, 2013;Michalak, et al, 2014;Nair et al, 2014;Peper et al, 2018). Rather than being inherently beneficial, persuasion science has revealed how the confidence that comes from feelings of power following thinking can magnify whatever mental content is accessible (Briñol, Petty, Durso, et al, 2017). For example, recent research has shown that feelings of confidence that come from power and other positive inductions can increase favorable self-evaluations Carroll et al, 2020) and physical performance (Horcajo et al, 2019) when people are thinking about their strengths, but decrease these self-evaluations and performance when they are thinking about their weaknesses.…”
Section: Is Empowerment Always Desirable?mentioning
confidence: 99%